Characterising fine-scale variation in plant species richness and endemism across topographically complex, semi-arid landscapes - Di Virgilio, G.; Wardell-Johnson, Grant; Robinson, Todd; Temple-Smith, D.; Hesford, J. (Elsevier, 2018)
The banded ironstone formation (BIF) ranges of south-western Australia are prominent landforms in a flat landscape and host a diverse flora. Plant diversity is expected to have a positive relationship with environmental heterogeneity in these ranges. However, there has been a lack of high-resolution data to assess how fine-scale environmental variation structures changes in plant communities across these ranges. We calculated species richness and corrected weighted endemism over 659 quadrats (each 400 m 2 ) and investigated their spatial distribution across BIFs in relation to 1 m resolution variables (microtopographic heterogeneity, solar radiation and topographic wetness) using geographically weighted regression. Microtopographic heterogeneity was most strongly related to richness and endemism, but this association was spatially variable at short distances across BIFs: relationships were negative or weakly positive on north-eastern range sections, whereas positive associations became progressively stronger further south and west on central, western and southern sections. Negative solar radiation-plant associations were reduced in these areas, likely because metre-scale surface variation moderates insolation. Topographic wetness-plant associations were negative on BIFs, but positive on the surrounding plains. The presence of fine-scale, geographically variant heterogeneity-diversity relationships in other locations would be difficult to detect if high-resolution environmental data are not used, with the implication that conservation decision-making may be compromised. Given climatic warming predicted for south-western Australia and other regions globally, a similar approach to that applied here can contribute to conservation by identifying locations likely to act as micro-buffers against warming.